How technological progress affects the carbon emission efficiency? Evidence from national panel quantile regression - Xie, Zihan; Wu, Rong; Wang, Shaojian (Journal of cleaner production, 2021)
In the social context of enhancing environmental quality and mitigating climate change, the improvement of carbon emission efficiency has emerged as a hot topic recently due to its promise as an approach to reduce emissions and improve environmental quality. A large volume of studies has identified technological progress as a critical factor affecting energy efficiency and pollution emission levels. From the perspective of national differences, the contributions of our study lied in constructing a system to measure technological progress based on the outputs and transformations of a country's technical progress level. Secondly, this paper examined the direct effect of technological progress on carbon emission efficiency, and the interaction effect between technological progress and energy intensity on carbon emission efficiency. Thirdly, we taking into account differences in the effect that technological progress can have on carbon emission efficiency in different national contexts. For this purpose, we evaluated the carbon emission efficiency of 59 countries in the period 1998–2016 using a super-SBM model, subsequently employing a national panel quantile regression method to explore the multiple effects of technological progress on the carbon emission efficiency of countries with different levels of efficiency. Our main findings indicate that the national carbon emission efficiency steadily increased across the study period, albeit with slight fluctuations, and that generally countries' carbon emission efficiency still exists great potential of enhancement. Technological progress will drive carbon emission efficiency to improve significantly, while this effect varies between countries with different levels of efficiency. Further, the interaction effects of technological progress and energy intensity are shown to exert complex effects on carbon emission efficiency, providing evidence that scientific and technological achievements need to be converted into productivity in time to offset the negative environmental effects of pollution and emissions. Governmental departments should, as a result, strengthen environmental supervision and urge enterprises to eliminate backward production capacity, introduce new technologies, and improve energy efficiency. Countries may realize the development of low-carbon sustainable societies by transforming their economic growth mode and adopting energy-saving production techniques.